Training needs assessment of fishermen in Oman through concept mapping technique. Issue 7 (2014) - Rakesh Belwal; Shweta Belwal; Omar Al Jabri
<x xml:space="preserve"> Abstract </x> Purpose – This study aims to assess the training needs of fishermen in Oman using the concept mapping technique. This study was the part of a larger research project on the training needs assessment (TNA), where a mixed method approach was used to identify the training needs. Design/methodology/approach – Perspective of 12 instructors on a focus question was taken during a brainstorming session at a Fishermen Training Institute in Oman. Using the concept mapping technique involving the multidimensional scaling and hierarchical cluster analysis, the data recorded was analyzed to arrive at the need clusters, which were later rated and ranked to assign relative importance. Findings – The identification led to a ten‐clustered solution, covering a range of areas, requiring technical and behavioral skills. The top five training concerns were also identified using the participants' ratings of the identified training‐need clusters. Furthermore, the merit of concept mapping technique over purely quantitative assessments was also realized. Research limitations/implications – The study not only identified and evaluated the training needs but also observed the relevance of concept mapping technique. It was observed that the concept mapping technique struck a balance between the two extremes of subjectivity and objectivity while identifying the training needs. The application of concept mapping technique can help in covering the concerns of multiple stakeholders in TNA. Practical implications – It identifies some key training areas for Fishermen Training Institutions and government bodies in Oman. The research also supports the extension of the application of concept mapping technique to decision‐making situations in other areas. Social implications – Training interventions based on the needs assessment will help fishermen from the Oman's Batinah coast in gaining additional skills, expertise and income. Originality/value – This study applies the concept mapping technique in assessing the training needs of fishermen. The research also shares the outcomes of a pioneering attempt to identify fishermen's training needs in Oman. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors thankfully acknowledge The Research Council of Oman (TRC) for awarding a financial grant to this research project. </ack>